Chimeric Antigen Receptor-Engineered T Cells for Immunotherapy of Cancer. (5th May 2010) - Cartellieri, Marc; Bachmann, Michael; Feldmann, Anja; Bippes, Claudia; Stamova, Slava; Wehner, Rebekka; Temme, Achim; Schmitz, Marc
Abstract : CD 4 + and CD 8 + T lymphocytes are powerful components of adaptive immunity, which essentially contribute to the elimination of tumors. Due to their cytotoxic capacity, T cells emerged as attractive candidates for specific immunotherapy of cancer. A promising approach is the genetic modification of T cells with chimeric antigen receptors (CARs). First generation CARs consist of a binding moiety specifically recognizing a tumor cell surface antigen and a lymphocyte activating signaling chain. The CAR-mediated recognition induces cytokine production and tumor-directed cytotoxicity of T cells. Second and third generation CARs include signal sequences from various costimulatory molecules resulting in enhanced T-cell persistence and sustained antitumor reaction. Clinical trials revealed that the adoptive transfer of T cells engineered with first generation CARs represents a feasible concept for the induction of clinical responses in some tumor patients. However, further improvement is required, which may be achieved by second or third generation CAR-engrafted T cells.